Elementos que conforman el servicio de transporte terrestre para el desarrollo de la competitividad del destino turístico trujillo - Nakayo Cabrera, Tsumico Noemi Hossana (2014)
This final report entitled elements of transport for the development of the competitiveness of Trujillo. Its field of study elements of transport service of the city of Trujillo This research comes against the interest of studying the aspects that make up the transport service for the competitiveness of the city of Trujillo as a destination. To conduct research took into account three variables, quality tourism services, security in tourism services, and tourism promotion is performed on the destination. To identify the elements of service tourist transport a sample of seven transport companies tourist Oltursa, CRUZ DEL SUR, MOBILE, LINE, ITTSA, TRC and FLORES, each company was visited and the mobility was observed, the campus facilities and services they offer, an accidental sample of 93 tourists who were surveyed about the perception they had of elements such as speed, quality of care and service on board, presentation, safety climate, comodida board was taken and finally the tourism promotion; which form the elements of tourist transport service Quality services offered by tourist transport companies are expressed in: speed, quality care and service on board and presentation. The security offered by tourist transport companies are expressed in: the climate of security and comfort on board Promoting tourism expresses the degree of commitment with the transport companies to their region spreading the attractions of the region as a tourist destination. Finally it is concluded that transport companies have a solid basis for the development of the competitiveness of Trujillo as a tourist destination in its quality services, security and tourism promotion.